Organic reactions (John Wiley & Sons, 2001)
Organic Reactions is a comprehensive series of volumes composed of chapters devoted to important synthetic reactions. Each chapter includes detailed procedures illustrating the significant modifications of the chemical reaction as well as tables including all the pertinent examples. Each reaction is presented with information about the conditions, products, and yields where available.